78th Scientific Conference. Section: Magnetic Soft Matter: Book of Abstracts - University of Latvia. 78th Scientific Conference (My University, 2020)
February 14th, 2020; University of Latvia. Faculty of Physics, Mathematics and Optometry; House of Science, Jelgavas 3, Riga, Latvia
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Magnetic Soft Materials; ofsoft matter systems; application of magnetic field; magnetic soft materials